Arts and culture as creative learning of students through cultural product design - Boonpracha, Jong (Creativity Studies, 2022)
The study explores whether a design activity could promote creative learning expression and development among students regarding arts and culture issues through cultural product design. Therefore, students engage in designing a cultural product model. The study aims to analyze their ability to develop arts and culture through sketches and an appearance model. The research project was conducted to observe students (aged 18–20 years) as they negotiated and shared creative ideas during the process of cultural product design, interaction with fellow students, and the design presentation. The results indicate that design activities significantly contributed to students’arts and culture learning by developing creative ideas through cultural product design. Moreover, students developed reasoning, communication, and collaboration skills during the development of their work.